Sustainable Acoustics: A Smart Cities approach - Pérez, Iván F.; Mendoza, Oscar; Acosta, Oscar; Hermida, Luis F.; Herrera, Marcelo (TECCIENCIA, 2020)
Communication and Information technologies have optimized several pro- cesses of our daily life. Environmental Acoustics has also beneﬁted from this progress with technological tools that have enabled the digitization of data representing noise polluted zones in the world. For this purpose, georeferentiation procedures and noise mapping strategies have become available to institutions, governments and also the population, empowering citizens for the decision making and generating intelligent societies known as Smart cities. The present Project presents these results on a def- inite zone where noise measurements and afterwards digitization of these data and visualization is performed. Finally, approaches to assess the impact of noise on the population by means of noise conﬂict zones and noise levels to which residents are exposed are studied.